Post-translational Modifications of the p53 Protein and the Impact in Alzheimer’s Disease: A Review of the Literature - Clark, James S.; Kayed, Rakez; Abate, Giulia; Uberti, Daniela; Kinnon, Paul; Piccirella, Simona (Frontiers in Aging Neuroscience, 2022)
Our understanding of Alzheimer’s disease (AD) pathogenesis has developed, with several hypotheses over the last 40 years, including the Amyloid and Tau hypotheses, respectively. More recently, the p53 protein, well-known as ‘the guardian of the genome,’ has gained attention for its role in the early evolution of AD. This is due to p53’s central role in the control of oxidative stress and potential involvement in both Amyloid and Tau pathways. p53 is commonly regulated by post-translational modifications (PTMs), which affect its conformation, increasing its capacity to adopt multiple structural and functional states, including those that can influence several processes in AD. The following review will explore the impact of p53 post-translational modifications (PTMs) on its function and consequential involvement in AD pathogenesis.